Observations of the Influence of Regional Beach Dynamics on the Impacts of Storm Waves on the Connecticut Coast During Hurricanes Irene and Sandy - Tait, James F.; Ferrand, Ezgi Akpinar (Learning from the Impacts of Superstorm Sandy, 2015)
The Connecticut shoreline is one of the most intensively developed in the country. In many locations, development has relied on the buffering capacity of broad beaches for protection against storms. Much of this development is at risk due to an insufficient understanding of regional beach dynamics. The coast is commonly regarded as “protected” by the presence of Long Island. Nonetheless, Irene and Sandy imposed significant property losses on coastal cities. The most severe damages were due to wave impact in areas with narrow beaches. Small differences (as little as 21 m) in beach width proved to be significant during these storms. Sheltering by Long Island does not prevent coastal erosion during local storms. In the long run, it does prevent the rebuilding of the beach during fair weather by limiting the energy available for shoreward transport. This dynamic makes the beaches naturally erosive and their buffering capacity transient at best.
Keywords: Beach erosion; Beaches; Buffering capacities; Coastal cities; Coastal erosion; Connecticut beach dynamics; Dynamics; Energy asymmetry; Erosion; Fair weather; Hurricane Irene; Hurricane Sandy; Hurricanes; Property loss; Storm wave impacts; Storm waves; Storms; Water waves; beach erosion; dept.egm; energy asymmetry; faculty_collection; storm wave impacts

Coastal sediment management as a response to intensifying storms and sea level rise: A case study - Tait, James; Orlowski, Ryan; Brewer, Jessica; Miller, Matthew D (Towards coastal resilience and sustainability, 2018)
In a period of rising sea levels and intensifying storms, enhancing coastal resilience and finding sustainable ways of living with the coast have become necessary concerns. Investigations of storm wave damage to coastal structures on the Connecticut shoreline during Hurricane Irene and Superstorm Sandy revealed that the width and height of frontal beaches were the most common denominator in mitigating the damages. One of the major problems, particularly for a state like Connecticut that has a highly developed coastline with systematically eroding beaches, is that the cost of beach nourishment projects is not only high but is increasing rapidly. The cost of beach nourishment at Prospect Beach in the town of West Haven is instructive. However, considering the importance of beaches and the costs of replenishment, rethinking Environmental Protection policies in favour of instituting regional and local sediment management practices may be in order. © 2019 selection and editorial matter, C. Patrick Heidkamp and John Morrissey.
Keywords: Beach nourishment; Beach nourishment projects; Beaches; Coastal sediments; Coastal structures; Common denominators; Sea level; Sea level rise; Sediment management; Shore protection; Storm waves; Storms; Sustainable development; dept.egm